CRISPR and RNA interference: revolutionary tools for extending food shelf life and ensuring safety - Sidhu, Amanpreet K.; Sharma, Madhvi; Shah, Priya; Sandhu, Simrandeep Kaur (Frontiers in Food Science and Technology, 2025)
In the global food sector, extending shelf life and ensuring food safety continue to be major concerns that call for innovative approaches that go beyond traditional preservation methods. RNA interference (RNAi) and CRISPR have become cutting-edge biotechnological techniques with enormous potential for food preservation. CRISPR-mediated gene editing allows for precise modifications in food crops, livestock, and microbial systems to delay ripening, increase resistance to oxidative stress, and suppress enzymes responsible for rancidity. We have tried addressed this by introducing a comparative analysis of CRISPR and RNAi efficiency across climacteric and non-climacteric fruits, highlighted emerging targets (e.g., ethylene-independent ripening regulators and cell wall-modifying enzymes), and identified critical gaps in regulatory frameworks and delivery methods in less-explored crops like guava and papaya. This integration aims to present a more forward-looking perspective beyond existing literature. Similarly, to improve food stability and manage post-harvest degradation, RNAi-based techniques help to silence genes. By reducing mycotoxin contamination, improving disease resistance in livestock and aquaculture, and focussing on foodborne pathogens, these technologies provide revolutionary solutions for food safety that go beyond preservation. Despite its potential, the commercialisation and adoption of gene-edited food items are heavily influenced by legal frameworks, ethical issues, and public opinion. The mechanics and uses of CRISPR and RNA interference in food safety and preservation are examined in this review, along with ethical and legal issues and potential future developments for these technologies to ensure sustainable food security.